2013
DOI: 10.1002/ieam.1444
|View full text |Cite
|
Sign up to set email alerts
|

More ecological ERA: Incorporating natural environmental factors and animal behavior

Abstract: We discuss the importance of selected natural abiotic and biotic factors in ecological risk assessment based on simplistic laboratory bioassays. Although it is impossible to include all possible natural factors in standard lower-tier ecotoxicological testing, neglecting them is not an option. Therefore, we try to identify the most important factors and advocate redesigning standard testing procedures to include theoretically most potent interactions. We also point out a few potentially important factors that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…While there is a long history of identifying the relevance of delayed effects of stressors (e.g., Abel, ; Liess, ), our results feed the increasing concern for delayed interactions among stressors as these are typically ignored in risk assessment (Segner, ; Bednarska et al ., ). The here‐identified strong delayed synergism with heat waves and food shortage will indeed not be detected in standard ecotoxicological testing of pesticides, even when executed at different temperatures (Bednarska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…While there is a long history of identifying the relevance of delayed effects of stressors (e.g., Abel, ; Liess, ), our results feed the increasing concern for delayed interactions among stressors as these are typically ignored in risk assessment (Segner, ; Bednarska et al ., ). The here‐identified strong delayed synergism with heat waves and food shortage will indeed not be detected in standard ecotoxicological testing of pesticides, even when executed at different temperatures (Bednarska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The increased toxicity of PFOS at the higher temperature was probably due to a faster uptake, absorption and bioaccumulation (Del Piero et al 2012). The observed temperature-dependent PFOS effects on risk recognition and fast-start performance of the fish provide further support to the appeal by Bednarska et al (2013) to include a range of realistic temperatures in standard eco toxicity tests. Our study indicates that PFOS as an environmental pollutant could have ecological consequences for wild fish by decreasing risk recognition and escape behaviors.…”
Section: Discussionmentioning
confidence: 54%
“…This is in agreement with other studies finding species specific effects of multiple stressors3031, suggesting that the exact effects of interactions depend on the experimental setup, as well as on the species investigated. This highlights the potential problems of extrapolating results from studies investigating interactions on one species to, e.g., community scale or to ecological risk assessments12, and thereby emphasizing the need for further studies using standardised methods and/or multiple species. Interestingly, we found that the effects of the different treatments on composite performance were largely similar in the two species (Table 1), albeit highly variable between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in underestimating the effect of multiple environmental factors on population persistency and the stability of communities4, a risk exemplified by the combination of thermal extremes and drought stress resulting from climate change10. The predictability and generalizability of responses to multiple environmental factors should be incorporated in general global climate change models11, and in ecological risk assessments212 for increased accuracy and prediction power of community assembly modelling6.…”
mentioning
confidence: 99%